Pengaruh Media Sosial Lemon8 Terhadap Pemenuhan Kebutuhan Informasi Mengenai Korean Fashion Style - Puspitasari, Dilla; Nugrahani, Rah Utami (Jurnal Pustaka Komunikasi, 2024)
Social media plays a vital role as a primary source of information, bringing the ability to spread information and introduce new things to its environment. This has an impact on the creation of more open and clear communication. The effect is a widening of the public's viewpoint, even beyond the borders of the country. One of the most popular cultural trends, especially among younger generations, is Korean Wave-inspired fashion. With the growing demand for information about Korean fashion, many people turn to search for it through social media. One platform that meets this need is Lemon8, a social media app that focuses on sharing and exploring lifestyle information, Korean Fashion Wave. The study aims to measure how much social media influence Lemon8 has on meeting Korean style information needs. The research method used was quantitative, with sampling through simple random samplings and involving 400 respondents. According to the hypothesis test, the influence of Lemon8 was significant with t counting far larger than the table. The study showed that Lemon 8 contributed to meeting the information needs of Korean fashion style, while the remaining were likely to be influenced by other variables not studied in this study.